Improving Interprofessional Communication Utilizing Obstetric Simulation Training. (October 2017) - Durst, Jennifer; Temming, Lorene; Gamboa, Christine; Tuuli, Methodius; Macones, George; Young, Omar
Abstract : BACKGROUND: Effective interprofessional communication requires clear, concise, and respectful participation from each provider. Simulation has been shown to improve teamwork and patient safety in nonobstetric fields. Whether the benefit of interdisciplinary participation in simulation extends to the obstetric population is unknown. METHODS: We conducted a prospective educational trial involving obstetric residents and L&D nurses. Participants were administered a pretest examining their perception of interprofessional communication and cooperation with responses measured on a Likert scale. Participants then underwent an obstetric simulation, watched their video-taped performance, participated in a structured debrief and educational session, and then repeated the simulation. Following the simulation, they were administered a posttest to assess changes in their perception of communication and cooperation. RESULTS: Eighteen L&D nurses and 17 obstetric residents participated in the trial. Following simulation, participants were more likely to report that they feel respect from other providers ( P =.0087), use closed-loop communication ( P <.001), designate a clear leader ( P =.0009), read back verbal orders ( P =.0002), conduct a nonaccusatory debrief ( P =.0491), and view both their communication and communication from others as clear and effective ( P =.0043 and P =.0042, respectively). DISCUSSION: Obstetric simulation can be used to improve effective interprofessional communication and cooperation. Continued use of interdisciplinary simulation in obstetrics should be encouraged to promote a commitment to patient safety.